Anti‐inflammatory effect of Rhein on ulcerative colitis via inhibiting PI3K/Akt/mTOR signaling pathway and regulating gut microbiota. (1st March 2022) - Dong, Lingling; Du, Hongling; Zhang, Minyue; Xu, Haiting; Pu, Xiulan; Chen, Qiyan; Luo, Ruifeng; Hu, Yichen; Wang, Yitao; Tu, He; Zhang, Jinming; Gao, Fei
Abstract: This study aimed to analyze the therapeutic effect of Rhein on ulcerative colitis (UC) in mice and its possible mechanism. LPS‐induced UC cell model and DSS‐induced UC mouse model were used to analyze the antiinflammatory effect of Rhein on UC in vitro and in vivo, respectively. Network pharmacology analysis was conducted to identify potential signaling pathways involved in Rhein treating UC, and the results were further confirmed through western blotting assay. 16sRNA sequencing was performed to study the regulatory effect of Rhein on gut microbiota in UC mice. As indicated by the results, Rhein could significantly inhibit the production of pro‐inflammatory cytokines (e.g., TNF‐α, IL‐6 and IL‐1β) in vivo and in vitro, and alleviate DSS‐induced UC‐associated symptoms in mice (e.g., colon shortening, weight loss, diarrhea and hematochezia). The PI3K/Akt/mTOR signaling pathway was predicted as the potential interacting protein of Rhein in the treatment of UC through network pharmacology analysis. It was found through western blotting assay that the Rhein treatment could significantly inhibit the PI3K/Akt/mTOR signaling pathway by decreasing the phosphorylated protein levels of PI3K, Akt, mTOR and p70S6K1. By 16sRNA gene sequencing analysis, Rhein administration could partially reverse the gut dysbacteriosis of mice induced by DSS and decrease pathogenic bacteria (e.g., Enterobacteriaceae and Turicibacter ). It was positively correlated with the production of pro‐inflammatory cytokines above, whereas the increase in probiotics (e.g., Unspecified‐S24‐7 and Rikenellaceae ) was negatively correlated with the production of pro‐inflammatory cytokines. In conclusion, Rhine had anti‐UC efficacy, which was demonstrated by mitigating the UC symptoms and reducing intestinal inflammation by inhibiting the PI3K/Akt/mTOR signaling pathway and modulating gut microbiota.